2011
DOI: 10.1097/rct.0b013e318219f810
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Fluorine 18 Fluorodeoxyglucose-Positron Emission Tomography and Positron Emission Tomography/Computed Tomography in Evaluating Patients With Mycobacteriosis? A Systematic Review

Abstract: (1) Mycobacteriosis commonly causes increased ¹⁸F-FDG uptake; therefore, positive ¹⁸F-FDG-PET results should be interpreted with caution in differentiating benign from malignant abnormalities. (2) ¹⁸F-FDG-PET and PET/CT are potentially useful in detecting sites of Mycobacterium infection. (3) Dual-phase ¹⁸F-FDG-PET is not useful for the differential diagnosis between malignant lesions and sites of Mycobacterium infection. (4) ¹⁸F-FDG-PET and PET/CT are useful for the evaluation of disease activity and in monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 18 publications
0
22
0
3
Order By: Relevance
“…It is common that false positivity on PET imaging is caused by tuberculous disease [13,14,15]. Orki et al [8] reported that patients with tuberculous pleuritis could have region of increased 18 F-FDG uptake in the pleura.…”
Section: Discussionmentioning
confidence: 99%
“…It is common that false positivity on PET imaging is caused by tuberculous disease [13,14,15]. Orki et al [8] reported that patients with tuberculous pleuritis could have region of increased 18 F-FDG uptake in the pleura.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the latest generation of high-resolution PET scanners is coupled with multidetector CT (PET/CT), allowing a simultaneous co-registration of morphological and functional data [11]. Activated inflammatory cells such as neutrophils, macrophages and lymphocytes present an increased FDG uptake, causing significant FDG accumulation during inflammation [12,13]. Hence, the slight specificity of FDG PET/CT emerges as a potential advantage in the management of patients with inflammatory or infectious diseases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Das Lymphknotenmuster ist gekennzeichnet durch einen erhöhten Uptake in vergrößerten mediastinalen und hilären Lymphknoten, wobei der Uptake höher ausfällt als der im Lungengewebe. Hierbei ist insbesondere auf extrathorakale Manifestationen zu achten, die beim Lymphknotenmuster häufi ger auftreten [ 67 ] . Weiterhin wird die PET als Ganzkörperszintigrafi e ausgeführt (jedenfalls vom Schädel bis inklusive des Beckens), wodurch ebenfalls die Detektion extrathorakaler Manifestationen ermöglicht wird, die in der CT geregelt übersehen werden.…”
Section: Pilzinfektionenunclassified